Vanara: The legend of Baali, Sugreeva and Tara - Anand Neelakantan (Penguin Books, 2018)
Baali and Sugreeva of the Vana Nara tribe were orphan brothers who were born in abject poverty and grew up as slaves like most of their fellow tribesmen. They were often mocked as the vanaras, the monkey men. Sandwiched between the never-ending war between the Deva tribes in the north and the Asura tribes in the south, the Vana Naras seemed to have lost all hope. But Baali was determined not to die a slave. Aided by his beloved brother, Sugreeva, Baali built a country for his people. The capital city, Kishkindha, became a beacon of hope for emancipated slaves from across the world. It was a city of the people, by the people, for the people, where there was no discrimination based on caste, creed, language or the colour of skin. For a brief period in history, it seemed as if mankind had found its ideal hero in Baali. But then fate intervened through the beautiful Tara, the daughter of a tribal physician. Loved by Baali and lusted after by Sugreeva, Tara became the cause of a fraternal war that would change history for ever. The love triangle between Baali, Tara and Sugreeva is arguably the world's first. Written by Anand Neelakantan who gave a voice to Ravana in Asura, Duryodhana in the Ajaya series and Sivagami in the Baahubali series, Vanara is a classic tale of love, lust and betrayal. Shakespearean in its tragic depth and epic in its sweep, Vanara gives voice to the greatest warrior in the Ramayana-Baali.